The effect of different LED light colors on the color performance of neon tetra (Paracheirodon innesi) - Samsu Adi Rahman; Erwin Wuniarto; Dicki Alif Saputra (Acta Aquatica: Aquatic Sciences Journal, 2026)
The neon tetra (Paracheirodon innesi) is a popular ornamental fish known for its unique colors. Neon tetras emit a blue neon color with a red gradient. However, the fish may experience color fading when kept for long periods. This study aims to investigate the effect of different colored LED lights on enhancing the color quality of neon tetra (P. innesi). The research was conducted from August to September at the Integrated Laboratory of Muhammadiyah University Luwuk. The study used a Completely Randomized Design (CRD) with four treatments: control (no light), Treatment A: (red LED), Treatment B: (blue LED), and Treatment C: (green LED). The color quality of the neon tetra was visually observed using a camera from a distance of 10 cm. The color data was analyzed using Adobe Photoshop version 25.9 by measuring the RGB values. The results showed that the use of different colored LED lights had a significant effect, with the best RGB red value of 43.33 and the best RGB blue value of 33.30. The conclusion is that red LED lights enhance the RGB red value, and blue LED lights enhance the RGB blue value in neon tetra colors. Keywords: LED Lights; Neon Tetra; Ornamental Fish; Paracheirodon innesi; RGB